Castor oil for induction of labour: a retrospective study. (18th August 2018) - Neri, Isabella; Dante, Giulia; Pignatti, Lucrezia; Salvioli, Chiara; Facchinetti, Fabio
Abstract: Purpose: The aim of this study is to investigate the safety and efficacy of castor oil to induce labour. Materials and methods: A retrospective observational case control study was conducted over five years. Castor oil was proposed to women referred to the Birth Centre (Castor Oil group (COG)). They were compared to women who chose to be followed by the traditional doctor-led unit (control group (CG)). Castor oil was administered in a 60 ml single dose in 200 ml of warm water. Inclusion criteria were gestational age between 40 and 41 weeks plus premature rupture of membranes between 12 and 18 hours or amniotic fluid index ≤4 or Bishop Score of ≤4 or absence of spontaneous labour over 41 + 4 weeks. Results: Pharmacological induction of labour was required for 18 women in the COG (45%) and 36 in the CG (90%) ( p  < .001). The mode of delivery differed significantly between groups: women assuming castor oil showed a higher incidence of vaginal delivery, whereas the incidence of caesarean section was lower in the COG, but no statistical significance was reached. Conclusions: The use of castor oil is related to a higher probability of labour initiation within 24 hours. Castor oil can be considered a safe non-pharmacological method for labour induction.